1984
DOI: 10.2355/isijinternational1966.24.7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Molten Iron Oxide and FeO Bearing Slags by H2-Ar Plasma

Abstract: Synopsis(I) Reduction of molten iron oxide and Fe0 bearing slag by H2 Ar plasma was studied using water cooled Cu crucible. The sample weights were 25 to 75g, the flow rate of mixture-gas was 20 1/mm n and DC electric power of plasma was 8.3 kW. Results obtained were as follows:(1) The reduction of molten iron oxides proceeds linearly with time and the reaction rate is proportional to the partial pressure of atomic hydrogen. Therefore, it is considered that the rate determining step is the chemical reaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 0 publications
5
28
1
Order By: Relevance
“…Badr [13] studied the characteristics of the HPSR process in terms of thermodynamics, kinetics, and the possibility of industrialization. His results have confirmed the observations of previous researchers [20,25,26].…”
Section: Thermodynamic Properties Of Thermal Plasmasupporting
confidence: 90%
See 1 more Smart Citation
“…Badr [13] studied the characteristics of the HPSR process in terms of thermodynamics, kinetics, and the possibility of industrialization. His results have confirmed the observations of previous researchers [20,25,26].…”
Section: Thermodynamic Properties Of Thermal Plasmasupporting
confidence: 90%
“…Kamiya et al [26] studied the reduction of molten iron oxide using H 2 -Ar plasma. They reported that the hydrogen utilization degree can be 60% at low concentration of hydrogen in the gas mixture.…”
Section: H 2 +mentioning
confidence: 99%
“…One of the main results was a lower degree of hydrogen utilisation (η H 2 ) when using a high concentration of hydrogen in the mixture of H 2 -Ar. Their results were in good agreement with the observations of other researchers [28][29][30][31][32]. In the present study, the concentration of hydrogen in the gas mixture was set to be constant.…”
Section: Introductionsupporting
confidence: 92%
“…One of the main results was a lower degree of hydrogen utilisation ( 2 ) when using a high concentration of hydrogen in the mixture of H2-Ar. Their results were in good agreement with the observations of other researchers [29][30][31][32][33]. In the present study, the concentration of hydrogen in the gas mixture was set to be constant.…”
Section: Introductionsupporting
confidence: 92%